A Note on a Camassa-Holm Type Equation - Coclite, Giuseppe Maria; Ruvo, Lorenzo di (Journal of Applied Nonlinear Dynamics, 2026)
Camassa-Holm equation arises as model for unidirectional propagation of shallow water waves over a flat bottom. In this paper, we prove the well-posedness of the classical solution for the Cauchy problem associated with this equation, for every choice of the time T.